“Cinética de degradación de la antocianina y estudio reológico de jugo concentrado de uva Isabella (visits labrusca)” - Arce Saavedra, Thony (2016)
Introduction. Grape from San Antonio de Cumbaza has similar sensory characteristics and composition to the black grapes produced in other regions, with a high demand for the regional wine production and as a flavoring for the food industry. The black grape generally provides phenolics, including anthocyanins with antioxidant properties in vitro and probably benefits to human health. Objective. Study the kinetics of degradation of anthocyanins and rheological properties of grape juice. Methods. Thermal degradation of anthocyanins was conducted at 70, 80 and 90ºC for 5, 1 O, 15 and 20 minutes rota evaporator mínimum vacuum pressure. Rheological study was performed with the Brookfield viscometer L VDV - III Ultra at different temperatures and concentrations. This data were adjusted to the Oswald-de-Waelle, Casson and Herschel-Bulkley mathematical models. Results. Anthocyanins and total phenols were quantified. Anthocyanins degradation for the proposed heat treatment was imminent. The rheological behavior produces values clase to Ostwald de Waele model and also a lower consistency index. Conclusion. Grape juice has a high content of total phenolics, highly sensitive thennal degradation, and a fluid type pseudoplastic rheological behavior.